Tree component dynamics in function of edge distance in an araucaria forest in "planalto sul catarinense" region, Brazil Dinâmica do componente arbóreo em função da distância da borda em uma floresta com araucária no planalto sul catarinense, Brasil - Gross A.* (2020)
© 2020, Universidade Federal de Santa Maria. All rights reserved.This study aimed to analyze the tree component dynamics in an araucaria forest in function of fragment edge distance in the Santa Catarina state, Brazil. To do so, we conducted the vegetation surveys in 2011 and 2015, through permanent plots, in five sampling transects, containing ten 200 m2 plots for each one. The first five plots (0-50 m) were defined as edge sector and the last five plots (50-100 m) were considered as interior sector. In 2011, tree individuals were surveyed, with the recruit and dead individuals counted in 2015. The rates of mortality and recruitment were determined, and the species were classified into regeneration guilds. The study showed that there was no difference in tree community dynamics between the analyzed sectors, but the regeneration guilds presented different performance in function of edge distance, with light-demanding species succeeding in edge and shade-tolerant species performing better in the interior. We conclude that forest fragmentation has the potential to impact negatively the tree component in Araucaria forest.